Growth forms of Parietaria debilis (Urticaceae) and Veronica persica (Plantaginaceae) - Dellaferrera, Ignacio Miguel (2014)
This work analyzes growth forms in V. persica and P. debilis, in order to identify their structural development under undisturbed conditions. Temporal and spatial variation in branching system, structural and developmental features as well as growth direction and foliar sequence were studied in plants grown from seed in growth rooms and in plants collected in the field. In both species, the main axis and the basal branches behave similarly, so they may be considered equivalent structures. All structures produced form a synflorescence. Along the main axis and the basal paraclades of V. persica, a basal branching zone and an inhibition zone was observed with opposite phylotaxis. At the end of axes a flower production zone of alternate phyllotaxis was found. Parietaria debilis lacks inhibition zone and showed, instead, a continuous type of branching. The specie showed a main axis and long branches up to sixth order and numerous short branches. It is in the latter where the floral branches developed. The growth form of these two species will have important implications for their behavior as crop weed, due to its high capacity to produce flower structures rapidly and widely ensuring continuous production of seeds.